2018
DOI: 10.1038/s41598-018-19153-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Community Composition and Functional Activity Associated with Lake Wetland Water Level Gradients

Abstract: The water regime is often the primary force driving the evolution of freshwater lakes, but how soil microbes responded to this process is far from understood. This study sampled wetland soils from a shallow lake that experienced water regime changes, Poyang Lake of China, to explore the features of bacterial and fungal community in response to water level changes. The soil physicochemical properties, T-RFLP based community structures and soil activities (including basal respiration, microbial biomass and enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…B). The significant influence of water level on soil physiochemical properties and microbial community structure of non‐hydrocarbon‐impacted forest and freshwater wetland soils have been previously demonstrated (Brockett et al ., ; Ma et al ., ). Thus, the selective presence of hydrocarbon waste, combined presence of standing water and lack of tillage at depths below 10 cm contribute to landfarm community structure.…”
Section: Discussionmentioning
confidence: 99%
“…B). The significant influence of water level on soil physiochemical properties and microbial community structure of non‐hydrocarbon‐impacted forest and freshwater wetland soils have been previously demonstrated (Brockett et al ., ; Ma et al ., ). Thus, the selective presence of hydrocarbon waste, combined presence of standing water and lack of tillage at depths below 10 cm contribute to landfarm community structure.…”
Section: Discussionmentioning
confidence: 99%
“…CLPP is a useful tool for assessing microbial community metabolic function and functional diversity in both terrestrial and aquatic environments [41][42][43]. CLPP, also known as carbon source utilization patterns of soil microbial communities, is assessed using a Biolog-ECO micro-plate (Category NO.…”
Section: Community Level Physiological Profilingmentioning
confidence: 99%
“…Previous studies have suggested that water level fluctuations could regulate the transformation of nutrients by changing bacterial activities in active erosion and transport zones 17,[20][21][22][23][24] . In seasonal lakes, drying and inundation cycles within a year can influence nitrogen cycling by regulating nitrogen metabolism pathways [25][26][27] , such as anammox, nitrification, denitrification, and nitrogen fixation [28][29][30] .Determining metabolic functions related to the nitrogen cycle of the microbial communities in seasonal lakes is essential for understanding their roles in biogeochemical processes related to nutrient cycles 2,3,31,32 and their response to water level fluctuations 24,27,33,34 . Previous study indicated that bacterial communities are distinct taxonomically and functionally in the dry-season and wet-season in Poyang Lake 24 .…”
mentioning
confidence: 99%
“…Previous studies have suggested that water level fluctuations could regulate the transformation of nutrients by changing bacterial activities in active erosion and transport zones 17,[20][21][22][23][24] . In seasonal lakes, drying and inundation cycles within a year can influence nitrogen cycling by regulating nitrogen metabolism pathways [25][26][27] , such as anammox, nitrification, denitrification, and nitrogen fixation [28][29][30] .…”
mentioning
confidence: 99%
See 1 more Smart Citation